Issues of forecasting local budget revenues and increasing revenues (Eurasian Research Bulletin, 2023)
In the article, in the conditions of economic development and liberalization, the issues of expanding the base of local budget revenues and improving the mechanism of local tax calculation, the current situation and the foreign experience of implementation in management are studied in depth. The need for a deep study of the conceptual basis of local budget revenues and the development of practical recommendations to ensure their stability was justified. Practical proposals and recommendations were offered regarding the importance of taxes in the formation of local budget revenues and the increase of local budget revenues and the expansion of the list of local taxes